2022
DOI: 10.3390/ijerph192215145
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Syndrome in Outpatients and Its Association with Viral Load

Abstract: Introduction: The COVID-19 pandemic is the result of the SARS-CoV-2 virus, which has caused more than 100 million infections and more than 2.5 million deaths worldwide, representing a serious public health problem. The gold method for detecting this virus is qRT-PCR, which is a semiquantitative technique where the viral load can be established through its cycle threshold (Ct). It has also been reported that COVID-19 generates long-term symptoms (post-COVID-19). Methods: After three months, a survey was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
8
2
Order By: Relevance
“…Female gender and the presence of a comorbidity did not have any influence on the rate of PSC syndrome, which was in contrast to previous findings [ 20 ]. Moreover, our study reported a lack of association of OSC and PSC with Ct values detected in the acute phase of infection, which contradicts with the data presented by Perez et al showing a negative correlation between the viral load and the number of the LC symptoms [ 22 ]. Additionally, age, which was also inversely correlated with LC symptoms in a recent report [ 23 ], was found to be a significant risk factor for neither OSC nor PSC in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Female gender and the presence of a comorbidity did not have any influence on the rate of PSC syndrome, which was in contrast to previous findings [ 20 ]. Moreover, our study reported a lack of association of OSC and PSC with Ct values detected in the acute phase of infection, which contradicts with the data presented by Perez et al showing a negative correlation between the viral load and the number of the LC symptoms [ 22 ]. Additionally, age, which was also inversely correlated with LC symptoms in a recent report [ 23 ], was found to be a significant risk factor for neither OSC nor PSC in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Although previous studies have indicated that the amount of SARS-CoV-2 viral load correlates with the presence of long COVID and the extent of its symptoms, the current study did not find this correlation [ 21 , 22 ]. What sets this study apart from its predecessors is its exclusive focus on hospitalized patients, its assessment of long-term COVID symptoms extending beyond three months post-illness, and its measurement of viral load using blood samples instead of nasal swabs, which were used in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies found that there is an association, but in other studies, no such relationship with viral load was found. The relationship between long-COVID and COVID-19 viral load is a topic of ongoing research and debate [ 21 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Importantly, there seems to be a poor relationship between the severity of COVID symptoms and the risk of Long COVID. 17,25 An obvious problem is that the definition of this syndrome is not yet well established, and reported studies do not use a uniform symptom description. 8 In our study, we limited the survey to 10 questions as one of the main goals was to achieve high response rates.…”
Section: Discussionmentioning
confidence: 99%